2009
DOI: 10.1007/s00198-009-1101-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional geometry of weight-bearing tibia in female athletes subjected to different exercise loadings

Abstract: High-impact, odd-impact, and repetitive low-impact exercise loadings were associated with thicker cortex at the distal tibia. At the tibial shaft, impact loading was not only associated with thicker cortex, but also a larger cross-sectional area. High-magnitude exercise loading did not show such associations at either site but was comparable to repetitive non-impact loading and reference data. Collectively, the relevance of high strain rate together with moderate-to-high strain magnitude as major determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 38 publications
4
91
2
4
Order By: Relevance
“…This indicated that bone mass accrual from early adulthood to middle age is direction specific, corresponding with the change of strains. This observation is consistent with the direction-specific changes of bone geometry and mass distribution in people subjected to different exercise loading, (26,27) and it corroborates the mechanostat paradigm. (28) During aging physical activity level dropped, as demonstrated by the difference in LTPA score between mothers and grandmothers.…”
Section: Discussionsupporting
confidence: 88%
“…This indicated that bone mass accrual from early adulthood to middle age is direction specific, corresponding with the change of strains. This observation is consistent with the direction-specific changes of bone geometry and mass distribution in people subjected to different exercise loading, (26,27) and it corroborates the mechanostat paradigm. (28) During aging physical activity level dropped, as demonstrated by the difference in LTPA score between mothers and grandmothers.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, leanness sport and sport impact type were not associated with low femoral neck geometry or estimated strength or low BMD, contrary to reports from other investigators [1, 41,46,60,61]. Undoubtedly, various loading impacts from different sports have an influence on bone integrity [46,60,61] as do the factors related to leanness sports, such as menstrual cycle disturbances [40].…”
Section: Discussionmentioning
confidence: 70%
“…Undoubtedly, various loading impacts from different sports have an influence on bone integrity [46,60,61] as do the factors related to leanness sports, such as menstrual cycle disturbances [40]. Other investigators studied primarily elite athletes or competitive athletes participating in specific sports [1, 41,46,60,61]; whereas, our data were obtained from a sample of competitive and recreational female athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported in cross-sectional studies of athletes using peripheral Quantitative Computed Tomography (pQCT), which describe a thicker cortex in the playing arm of tennis players [20], the tibia of triple jumpers [21] and in athletes from impact sports [22] compared with matched controls, with little or no differences in density [23].…”
Section: Introductionmentioning
confidence: 86%